Long Relationship of Suffering with the Incidence of Diabetic Neuropathy in Diabetes Mellitus Patients at the South Bulango Health Center, Bone Bolango Regency - Nikma Suryana Harun; Vivien Novarina Kasim; Nirwanto Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Diabetes mellitus is a chronic disease characterized by an increase in blood glucose levels in the long term due to insulin disorders and is a growing public health problem. Prolonged hyperglycemia can lead to a variety of complications, including diabetic neuropathy, through peripheral nerve damage and microcirculatory disorders. Therefore, the length of suffering from diabetes mellitus needs to be studied as a factor that plays a role in the occurrence of diabetic neuropathy to support prevention and early detection efforts. This study aims to determine the relationship between the length of time suffering from diabetes mellitus and the incidence of diabetic neuropathy in patients who are treated at the South Bulango Health Center. The study used a quantitative approach with a cross sectional design and involved 116 respondents who were selected through proportional stratified sampling techniques. The research instrument used was the Diabetic Neuropathy Symptom Score (DNS) questionnaire. The results showed that respondents had diabetes mellitus for a long time <5 years, as many as 48 respondents (41.4%) had diabetic neuropathy and 37 respondents (31.8%) did not experience diabetic neuropathy. Meanwhile, in respondents with diabetes mellitus for a long time ?5 years, most of them had diabetic neuropathy, namely 27 respondents (23.2%), and only 4 respondents (3.4%) did not experience diabetic neuropathy. The results of the statistical test using the chi-square test obtained a p-value of 0.002 (<0.05), which shows that there is a significant relationship between the length of suffering from diabetes mellitus and the incidence of diabetic neuropathy in patients with diabetes mellitus at the South Bulango Health Center.